(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We studied the effect of ovalbumin on Candida albicans by agar well difussion method, OVA showed Anifungul activity against all studied cultured. Candida albicans is a, commensal yeast, fungus of the human oral, gastric, vaginal mucosal surfaces, and skin. C. albicans may become an opportunistic, pathogen and lead to life systemic, infections, severe mucocutaneous illnesses, and/or antibiotic-, induced dysbiosis, immunodeficiency, and/or medical procedures that disrupt protective host defense mechanisms and/or damage the integrity of the mucocutaneous barrier.